2021
DOI: 10.1080/10717544.2021.1902020
|View full text |Cite
|
Sign up to set email alerts
|

Electrosprayed minocycline hydrochloride-loaded microsphere/SAIB hybrid depot for periodontitis treatment

Abstract: Minocycline hydrochloride (MINO) has been one of the most frequently used antibiotics in the treatment of periodontitis due to its antibacterial activity and osteogenesis effects; however, high levels of MINO administered during the treatment halt the formation of new bone. Therefore, the purpose of the present study was to prepare a MINO-microsphere/sucrose acetate isobutyrate (SAIB) hybrid depot to reduce the burst release of MINO and ensure antibacterial and osteogenesis effects of MINO in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
2
10
0
1
Order By: Relevance
“…Solvent ratio Solvents Amount of minocycline (mg) (1082 cm −1 ) bands in PLGA as seen by others (Fu et al, 2017;Zhang et al, 2021). As seen by Zhang et al (2021), the minocycline sample had the characteristic -COOH (1650 and 1600 cm −1 ) and multiple complex peaks associated with the four benzene rings in minocycline (500-1400 cm −1 ). The minocycline-loaded PLGA microparticles had both the PLGA and minocycline associated bands and peaks.…”
Section: Microparticles and Decant Powder Compositionmentioning
confidence: 79%
See 2 more Smart Citations
“…Solvent ratio Solvents Amount of minocycline (mg) (1082 cm −1 ) bands in PLGA as seen by others (Fu et al, 2017;Zhang et al, 2021). As seen by Zhang et al (2021), the minocycline sample had the characteristic -COOH (1650 and 1600 cm −1 ) and multiple complex peaks associated with the four benzene rings in minocycline (500-1400 cm −1 ). The minocycline-loaded PLGA microparticles had both the PLGA and minocycline associated bands and peaks.…”
Section: Microparticles and Decant Powder Compositionmentioning
confidence: 79%
“…The absence of additional FTIR peaks in both the minocycline-loaded PLGA microparticles and the residue obtained after evaporation indicates that the interaction between PLGA and minocycline was due to physical blending rather than chemical conjugation (Zhang et al, 2021). When the evaporation collection method was utilized, the size of the particles increased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that SAIB is an efficient material to control the burst release of drugs from sustained release systems ( Lin et al, 2012 ; Lin et al, 2015 ). In our previous studies, we successfully designed an SAIB-based hybrid depot that significantly reduced initial drug release from 66.18% to 2.92% ( Zhang et al, 2021 ) and from 63.20% to .00% ( Zhang et al, 2020 ). Thus, in this study, we first prepared Ng liposomes using the film hydration method and characterized their properties, including their drug-encapsulation efficacy, morphology, size distribution, and drug release.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Meanwhile, the surgical process would bring patients fear and discomfort. [ 3 ] As an alternative, antibiotics, such as minocycline, [ 4 ] metronidazole, [ 5 ] and tinidazole, [ 6 ] have shown promising potential in treating periodontitis. [ 7 ] Especially by simply adding these antibiotics to ointments and applying the resultant ointments to the target area, the release of antibiotics would kill the pathogens effectively, bringing about complete inflammatory eradication.…”
Section: Introductionmentioning
confidence: 99%